Everyday religion observing modern religious lives - Ammerman, Nancy Tatom 1950- (Oxford, [England] Oxford University Press, 2007)
"Nancy T. Ammerman has assembled a diverse and interdisciplinary group of scholars to provide a critical observation of modern religion in action. This collection of previously unpublished essays approaches modern religion at its most fundamental levels and brings the reader into the presence of religious practice among the complexities of daily life. The authors take aim at the failure of secularization theories to explain why and how people continue to choose religion in the midst of modernity. Each essay combines portrait of religious activity in often unexpected places with an evaluation of currently dominant theories to offer a fresh alternative perspective. From media to politics to family and civic life, these scholars look for the ways religion crosses boundaries and compare its effects in different cultural and institutional situations."--Jacket.
Foreword / Peter L. Berger -- Introduction : observing modern religious lives / Nancy T. Ammerman -- Vicarious religion : a methodological challenge / Grace Davie -- Religion as communication : the changing shape of Catholicism in Europe / Enzo Pace -- The new voluntarism and the case of unsynagogued Jews / Lynn Davidman -- Religion, twice removed : exploring the role of media in religious understandings among "secular" young people / Lynn Schofield Clark -- Virtually boundless? : youth negotiating tradition in cyberspace / Mia Lövheim -- Redefining the boundaries of belonging : the transnationalization of religious life / Peggy Levitt -- When a funeral isn't just a funeral : the layered meaning of everyday action / Ziad Munson -- A place on the map : communicating religious presence in civic life / Paul Lichterman -- Connections and contradictions : exploring the complex linkages between faith and family / John P. Bartkowski -- Beyond literalism : reflexive spirituality and religious meaning / Kelly Besecke -- Embodied practices : negotiation and resistance / Meredith McGuire -- Touching the transcendent : rethinking religious experience in the sociological study of religion / Courtney J. Bender -- Studying everyday religion : challenges for the future / Nancy T. Ammerman.
Includes bibliographical references and index.
Keywords: Religion and sociology